MIMO Self-Encoded Spread Spectrum with Iterative Detection over Rayleigh Fading Channels - Shichuan Ma; Lim Nguyen; Won Mee Jang; Yaoqing (Lamar) Yang (Journal of Electrical and Computer Engineering)
Self-encoded spread spectrum (SESS) is a novel communication technique that derives its spreading code from the randomness of the source stream rather than using conventional pseudorandom noise (PN) code. In this paper, we propose to incorporate SESS in multiple-input multiple-output (MIMO) systems as a means to combat against fading effects in wireless channels. Orthogonal space-time block-coded MIMO technique is employed to achieve spatial diversity, and the inherent temporal diversity in SESS modulation is exploited with iterative detection. Simulation results demonstrate that MIMO-SESS can effectively mitigate the channel fading effect such that the system can achieve a bit error rate of 10−4 with very low signal-to-noise ratio, from 3.3 dB for a 2×2 antenna configuration to just less than 0 dB for a 4×2 configuration under Rayleigh fading. The performance improvement for the 2×2 case is as much as 6.7 dB when compared to an MIMO PN-coded spread spectrum system.